Bridging the divides of online reporting - Brown, Alistair (Elsevier, 2007)
This paper looks at the possibilities of improving online reporting by closing the ‘digital divide’ through a ‘digitalised revolution’ and by narrowing the ‘accounting divide’ through the sharing of power and the expansion of membership in the International Accounting Standards Board (IASB). Paradoxically, whilst the IASB may have contributed to the ‘accounting divide’ it may very well possess the potential to close it and thus improve online reporting. The potential to bridge the ‘accounting divide’ rests with the greater participation by developing country members to exert influence and ownership of the accounting standards setting process.